Institutional and geopolitical dynamics shaping the internationalization of Finnish firms in the U.S. market - Ruuskanen, Joel (My University, 2026)
For Finnish companies, internationalization toward the United States is driven by both strategic growth objectives and broader institutional and geopolitical developments. Due to Finland’s small domestic market and export-oriented economic mode, expanding abroad is a structural necessity. The United States represents a significant destination market, particularly for firms in technology, manufacturing and clean energy sectors, but presents a considerably different institutional environment. The theoretical framework of this thesis draws on institutional theory and the institution-based view (IBV), which together provide a lens for examining how formal regulations, informal norms and geopolitical alignments shape firms’ strategic behavior. The findings show that institutional distance between Finland and the United States is most evident in the decentralized regulatory system, the competitive legal environment and the assertive business culture characteristics of the U.S. market. At the same time, Finnish firms benefit from their home-country institutional heritage, including stable governance, high trust and strong sustainability competencies, which enhance perceived legitimacy in the United States. Geopolitically, Finland’s accession to NATO and the strengthening of transatlantic cooperation reduce political distance and reinforce trust-based business relations, especially in security, defense, technology and clean energy industries. This thesis contributes to institutional theory by examining how firms from small advanced economies navigate complex institutional environments and offers practical insights for Finnish companies seeking to build legitimacy, adapt strategically and leverage institutional complementarities in the U.S. market.
Keywords: internationalization, institutional theory, institution-based view, institutional distance, geopolitical environment, Finnish firms